2022
DOI: 10.3390/ma15030874
|View full text |Cite
|
Sign up to set email alerts
|

Natural Cellulosic Fiber Reinforced Concrete: Influence of Fiber Type and Loading Percentage on Mechanical and Water Absorption Performance

Abstract: The paper reports experimental research regarding the mechanical characteristics of concrete reinforced with natural cellulosic fibers like jute, sisal, sugarcane, and coconut. Each type of natural fiber, with an average of 30 mm length, was mixed with a concrete matrix in varying proportions of 0.5% to 3% mass. The tensile and compressive strength of the developed concrete samples with cellulosic fiber reinforcement gradually increased with the increasing proportion of natural cellulosic fibers up to 2%. A fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…This may indicate that the accessible volume of pores is reduced in the presence of fibers as a result of the alleviation of the hydrophilic property of fibers by the alkali treatment, increasing their surface roughness and adhesion in the concrete matrix [57]. The observed decrease in TWA in the tested concrete mixes is fully in line with results reported by Jamshaid et al [58] on water absorption capacity of the natural cellulosic fiber-reinforced concrete mixes with different plant fibers and varying loading ratios of fibers. Findings revealed that mixes with up to 2% fiber loading ratios had a reduced absorption capacity, as compared to plain concrete, enhancing the durability and stability of mixes.…”
Section: Total Water Absorptionsupporting
confidence: 90%
“…This may indicate that the accessible volume of pores is reduced in the presence of fibers as a result of the alleviation of the hydrophilic property of fibers by the alkali treatment, increasing their surface roughness and adhesion in the concrete matrix [57]. The observed decrease in TWA in the tested concrete mixes is fully in line with results reported by Jamshaid et al [58] on water absorption capacity of the natural cellulosic fiber-reinforced concrete mixes with different plant fibers and varying loading ratios of fibers. Findings revealed that mixes with up to 2% fiber loading ratios had a reduced absorption capacity, as compared to plain concrete, enhancing the durability and stability of mixes.…”
Section: Total Water Absorptionsupporting
confidence: 90%
“…Then, structural analysis is performed. The required steel reinforcement is then calculated to enhance the mechanical performance of structural elements such as ductility, tensile strength, and creep resistance [ 2 , 3 , 4 , 5 , 6 , 7 ]. Finally, the ultimate limit state and serviceability limit state requirements provided by design codes are checked [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the flexural strength of coconut-fiber-reinforced cementitious composites, most studies have reported increased flexural strength [243][244][245][246]272]. In a similar way, the majority of studies have reported enhancements in the flexural strength of jute- [247,248,251,273,274] (Figure 18d), hemp-[252-254] (Figure 18e), sisal- [4,256,275] (Figure 18f), pineapple- [83,258,260] (Figure 18g), sugarcane-bagasse- [4,263,275] (Figure 18h), and flax- [264][265][266][267] (Figure 18i) fiber-reinforced cementitious composites, compared to control specimens/composites. Overall, it may be concluded that, in comparison to compressive strength, the effect of fiber is more significant with respect to enhancements in the flexural strength of cementitious composites.…”
Section: Flexural Strengthmentioning
confidence: 79%